Consumer Protection in Live Streaming-Based Commercial Transactions - Yanti Yulianti (Gudang Jurnal Multidisiplin Ilmu, 2025)
The rapid evolution of digital technologies, particularly live streaming features in e-commerce platforms, has significantly transformed consumer behavior while introducing new risks to consumer protection. Live streaming based commercial transactions often involve real time, visually driven interactions that encourage impulsive purchasing decisions, making traditional regulatory frameworks insufficient. This study aims to analyze the primary factors influencing consumer protection in live commerce settings by examining five core variables: product transparency, platform accountability, perceived risk, consumer trust, and digital literacy. Utilizing a qualitative exploratory approach, this research conducted a comprehensive literature review of 77 international journal articles published between 2020 and 2024. The findings indicate that product transparency and platform accountability are fundamental to enhancing consumer trust and reducing perceived risks, whereas digital literacy acts as a moderating factor that empowers consumers to make informed decisions. The study proposes a conceptual framework that integrates behavioral and regulatory dimensions, offering both theoretical insights and practical implications for improving consumer protection in fast paced, interactive digital marketplaces.